If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(7 + n) = 40 (7 * 2 + n * 2) = 40 (14 + 2n) = 40 Solving 14 + 2n = 40 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 2n = 40 + -14 Combine like terms: 14 + -14 = 0 0 + 2n = 40 + -14 2n = 40 + -14 Combine like terms: 40 + -14 = 26 2n = 26 Divide each side by '2'. n = 13 Simplifying n = 13
| 3.7x-2.2=16.3 | | 1.62y=3.14(y-8.62) | | 5(2x-3)-6x=0.5(4x+10) | | 10m-50+20p=0 | | f(x)=x^2+4x-32 | | -7x+12=x-6 | | n+n+56=180 | | 3(5+n)=150 | | 2x+0=7 | | -5m-3=3+5m | | 2x-3.8+x=62 | | 8(4+n)=88 | | 3-bc=35 | | 5(3+n)=88 | | -2(p+1)+3=-15 | | 3x^2-6x+6x=0 | | 5(3+n)=90 | | g(0)=3(0)+2 | | (.0309+x)+27.1594637= | | 6x-3x+26=5(x+8) | | -2a+3=-2 | | 3ln(x)=15 | | 2*9-4+8*2=288 | | 5q=2p | | 10+3b-7b= | | m-2n=0 | | 3(4+n)=21 | | (4x+4)+(5x-3)+17=3x*4 | | x^2-5x+9x-12=180 | | 3(.3x+.1)+.2x= | | 3x^2+15x-108=0 | | 5p+9=2n |